Local atopy is more relevant than serum sIgE in reflecting allergy in childhood adenotonsillar hypertrophy. Issue 5 (3rd June 2013) - Zhang, Xiaowen; Sun, Baoqing; Li, Shuai; Jin, Hui; Zhong, Nanshan; Zeng, Guangqiao
Abstract: Background: There was a lack of convincing evidence supporting the influence of allergy on the adenotonsillar hypertrophy (ATH). We investigated the presence of specific IgE (sIgE) in the serum and adenotonsillar tissues in children with ATH. Methods: A Pharmacia ImmunoCAP system was used to test sIgE against 31 allergens in the serum in 83 children with ATH before adenotonsillectomy. sIgE against 15 representative allergens were detected in adenotonsillar tissues from 20 of those children. Results: A total of 51 (61.45%) children had positive serum sIgE. 20 children with ATH had positive sIgE to more than two allergens at both tonsils and adenoids, although half of them were serum sIgE negative. The percentage of subjects with positive sIgE expression in adenoids and tonsils was 50.0% and 42.9%, respectively, among the subjects with positive serum sIgE expression. Of subjects with negative serum sIgE expression, local sIgE was detected in 36.0% of adenoids and 43.8% of tonsils, respectively. The rate of sIgE presence in local tissue (adenoids or tonsils) was significantly higher than that seen in the serum. Conclusion: This study provided evidence that there was an important role for allergic inflammation in the ATH. The inconsistency in sIgE expression between adenotonsillar and serum suggests a role of local atopy in childhood ATH.